Parables of Freedom and Necessity - Abdelwahab M. Elmessiri (International Institute of Islamic Thought, 1996)
Epilogue Geoffrey Chaucer’s ‘The Frankeleyn’s Tale” and Bertold Brecht’s The Exception and the Rule seem to have very little in common. Chaucer’s medieval narrative poem tries to follow the norms of its genre and fulfiil the reader’s expectations, whereas Brecht’s modernist experimental play violates many of the rules of drama laid down by Aristotle and other classical critics. It deliberately shocks the reader out of any facile identification with the characters as well as any willing suspension of disbelief. But despite their many obvious differences, this study argues that their similarities are quite relevant and significant. Both works deal with the themes of human freedom, moral responsibility, and ability to transcend. These are among the major themes of literature throughout time-but they have acquired particular poignancy in our modern time with the rise and gradual unfolding of what I term the “Paradigmatic sequence of secularization.” Since the terms “paradigm” and “secularism” are already quite problematic, and to talk of “a paradigmatic sequence of secularization” is even more so, some kind of clarification and even redefinition is in order. Paradigms When a critic singles out two literary works for comparison, the choice is not guided by some universally established objective rules, but rather dictated by a certain set of assumptions, norms, criteria, biases, and so on. When he/she engages in the critical act itself, pointing out structural and thematic relations (of similarity and dissimilarity), he/she does ...